Ser moda. Apuntes sobre los modos de afirmarse en el mundo o en el mercado de las identidades - Abruzzese, Alberto (Pensar la Publicidad. Revista Internacional de Investigaciones Publicitarias, 2011)
In this paper the meaning of «being fashion» and of «being fashionable» is analyzed. This expressions are related to the concepts «being» and «appearance», to the natural behavior of «the one that is» and the artificiality of «the one that creates» a social identity. The author uses sociologist Georg Simmel’s theory to analyze the role of fashion in modern society. He describes the characteristics and contradictions of fashion such as creating social membership and differentiating the subject within the group.